2018
DOI: 10.1002/bio.3435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triazole‐tryptophan hybrid on the conformation stability of bovine serum albumin

Abstract: The effect of a potent antimicrobial compound bearing 1,2,3-triazole core and a tryptophan tail, triazole-tryptophan hybrid (TTH), with bovine serum albumin (BSA) have been explored using various spectroscopic and molecular docking methods. Studies revealed that TTH strongly quenches the intrinsic fluorophore of BSA by a static quenching mechanism. Time-resolved fluorescence spectra further confirmed the involvement of static quenching for TTH-BSA system. The calculated thermodynamic parameters; ΔH, ΔS, and ΔG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…When Δλ is 15 nm, the fluorescence intensity of the Tyr residue of BSA did not change regularly with K4 concentration. These results suggested that the conformation of the Trp residue was more affected than Tyr upon BSA– K4 interaction …”
Section: Resultsmentioning
confidence: 85%
“…When Δλ is 15 nm, the fluorescence intensity of the Tyr residue of BSA did not change regularly with K4 concentration. These results suggested that the conformation of the Trp residue was more affected than Tyr upon BSA– K4 interaction …”
Section: Resultsmentioning
confidence: 85%
“…Obtaining 3D fluorescence data by simultaneously varying both excitation and emission wavelengths across a range offers valuable information about structural changes in the protein . The 3D spectra of BSA and BSA in complexation with gartanin and friedelin are shown in Figure .…”
Section: Resultsmentioning
confidence: 98%
“…Obtaining 3D fluorescence data by simultaneously varying both excitation and emission wavelengths across a range offers valuable information about structural changes in the protein. 43 The 3D spectra of BSA and BSA in complexation with gartanin and friedelin are shown in Figure 9 . In Figure 9 A, peak A and peak B arise due to first-order Rayleigh scattering (λ ex = λ em ) and second-order Rayleigh scattering peak (λ ex = 2em), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations